Pembuatan Model Turbin Air Dengan Sistem Sirkulasi Tertutup - Muh Anhar (Indonesian Society of Applied Science, 2022)
Modern society is very attached to technological advances, With community technology can easily meet energy needs, one example is the electrical energy processing of energy conversion machines using turbine energy.The purpose of this manufacture is to find a solution to meet the need for electrical energy, as well as solving problems encountered in areas where there is no stream or waterfall.. as for the methodology in making this includes time and place, tools making, Tools and Materials and Methods of execution of Flow diagrams.The calculation result for effective head = 0.3 m, with the water discharge used to move the runner Q = 0.00033836 m3/s, obtained power generated for 0,87 Watt. With the data planned, the main dimension of Pelton type turbine is the outer diameter of the runner Do = 435.28 mm, diameter of D = 400 mm, the number of bowl z = 59 pieces with 1 nozzle